BOOK REVIEW: Sheila Fitzpatrick, “The Shortest History of the Soviet Union”, Ed. Black Inc, Columbia, 2022, 256 p. - MUREŞAN, Tudor (Studia Universitatis Babeș-Bolyai Historia, 2022)
The shortest History of the Soviet Union, written by Sheila Fitzpatrick, was published in the year of 2022, at the Black Inc. Books publishing house. The author is an illustrious historian of Austrian origins, whose main subjects of research include the history of the Soviet Union and of modern Russia. She is the leader of the revisionist school of history, applying in her works the perspective of history from below. She is also a Professor at the Australian Catholic University of Melbourne, Honorary Professor at Sidney University and Merituous Professor at Chicago University. The present work integrates 256 pages and is divided in seven chapters that present the history of the Soviet Union, starting with how it was founded after the First World War and until its fall, in 1991.